Synthesis, Characterisation And Evaluation Of Biocompatible Disulphide Cross-Linked Sodium Alginate Derivative Nanoparticles For Colon Targeted Drug Delivery - Ayub, Asila Dinie (2018)
Colon specific nano-drug delivery is a challenging system for a drug to reach the colon target site without any release along the stomach and small intestines. The application of layer-by-layer (LbL) on nanoparticles surface coating has been applied to improve the colon targeted oral drug delivery of insoluble drugs. Here, we aimed to formulate a self-assembly cysteamine-based disulphide cross-linked sodium alginate (SA) (with LbL) to improve the delivery of paclitaxel to colonic cancer cells to promote oral chemotherapy. Cysteamine was conjugated to the backbone of oxidised SA to form a core of self-assembly disulphide cross-linked nanospheres.